Huracanes y biodiversidad costera tropical - Salazar-Vallejo, Sergio I (Revista de Biología Tropical, 2002)
Tropical coastal biodiversity has been modulated by tropical storms during a long time and it is currently facing a heavy human impact. The purpose of this review is to compile the available information to improve our understanding of hurricane impacts and to promote the establishment of coastal landscape monitoring, because that is the best way to assess these impacts. Although generalizations on hurricane effects are elusive, some historical dynamics and temporal relationships are included and some details are presented on the impacts by resuspension and movement of sediments, storm waves, and breaking off of coral reef organisms. Some effects on marine turtles and coastal forests are also briefly pointed out